Influence of reactor material and activated carbon on the thermocatalytic decomposition of methane for hydrogen production - Abbas, Hazzim F.; Daud, Wan Mohd Ashri Wan (Elsevier, 2010)
A series of experiments was conducted to study the catalytic effects of the stainless-steel reactor material and activated carbon (AC) on the decomposition of methane for production of hydrogen. Additionally, the effects of the methane flow rate, amount of AC, decomposition temperature, and particle size on methane conversion, initial decomposition rate and deactivation time were determined in a fixed bed reactor. The reactor wall seriously affected the methane decomposition when the temperature was higher than 850 degrees C. The activity of the AC increased with the increase in methane decomposition temperature (775-850 degrees C), and changing the particle size (135-1095 mu m) did not have a significant effect. The initial rate of methane decomposition showed an inverse and non-linear relationship with increasing weight of AC due to the dilution of methane by the produced hydrogen. However, the method of changing the volume hourly space velocity, i.e., by changing either the AC weight at a constant methane flow rate or the methane flow rate at a constant AC weight, did not cause differences in the measured AC initial activity. Various measurements on the AC at the beginning and end of the experiment revealed that methane decomposition occurs mainly within AC micropores. (C) 2010 Elsevier B.V. All rights reserved.